AKTIVITAS PENGAJARAN MELALUI PENDEKATAN EKSISTENSIALISME - Hilmi Hilmi (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2013)
Instructional activities which have been existed since the human existence on the earth is always in ongoing developments and progress. Among the factors that influence the development and advancement in the teaching is because of the emergence of various philosophical schools of thought as the creation of the philosophers. The flow of the existentialism spearheaded by Soren Aabye Kierkegaad also contributes a nuance of the teaching advancement significantly. The model of non-formal education and long life education is a form of precise enough offering in order that the human being gets the opportunity to act in accordance with its individual existence concretely.